Virtues of SIN: Effects of an immigrant workplace introduction program - Olof Åslund; Per Johansson (Institute for Labour Market Policy Evaluation (IFAU), 2006)
We evaluate an immigrant workplace introduction program aimed at helping individuals considered employable but at the same time expected to experience substantial difficulties in finding work. Using supported employment methods, the SIN program may influence outcomes through several channels. We use in-dividual data and a difference-in-differences approach to estimate the effects of the program. The results suggest that the program increased transitions from unemployment to work experience schemes, and improved future employment probabilities for those who entered these schemes.
Keywords: J61; J64; J68; 330; Unemployment; labor market programs; immigrants; Migranten; Arbeitsmarktpolitik; Schweden